Níveis de reabsorção óssea na periodontite induzida por ligadura em camundongos utilizando fios de seda e algodão - Aragão, Maria Márcia Marques da Silva (2023)
Induced periodontitis in rodents has been widely used to understand bone metabolism, particularly to assess conditions whose resorption is due to the installation of an inflammatory process, as it is characterized as a model that results in alveolar bone resorption (ABR). Thus, the objective was to compare the different levels of ABR at different times of euthanasia using cotton and silk threads in periodontitis induced by ligation in the mandible of mice. 78 male Swiss mice were used, after approval by the Committee on Ethics in the Use of Animals (09/20). Periodontitis was induced by inserting a silk or cotton thread in the mandibular first molars, and the animals were euthanized after 3, 5, 7, 11, 14 and 21 days. ABR was evaluated by macroscopy and the gingiva was removed for quantification of TNF-α levels by EILSA. Blood samples were obtained for measurement of serum levels of bone alkaline phosphatase (BALP). The weight of the animals was evaluated immediately before the placement of the ligature and at the moment before euthanasia. Significant (p<0,05) ABR was observed, in relation to Naive, in animals in which periodontitis was induced with cotton thread, from day 5, with a maximum peak at day 11. In the group induced with silk thread, this ABR was significant (p<0,05) from day 7 onwards, compared to Naive. In addition, on days 3 and 5, the ABR was higher (p<0,05) in animals with cotton thread, compared to those with silk thread, being similar in the other moments of euthanasia. Regarding TNF-α levels, no significant changes were observed in any of the threads compared to Naive. Furthermore, there was a significant increase (p<0,05) in BALP compared to Naive, only in the cotton group, at 11 days. Systemically, no significant changes were observed in the weight variation of animals submitted to periodontitis when compared to Naive animals. It can be concluded, therefore, that the ABR is achieved both with the use of silk and cotton threads, however, it is established earlier when using cotton thread.